Comparison of histochemical methods for the analysis of eosinophils and mast cells using a porcine model of eosinophilic esophagitis - Snider, Douglas B.; Meyerholz, David K.; Dellon, Evan S.; Cortes, Lizette M.; Karri, Akash; Blikslager, Anthony T.; Laster, Scott; Käser, Tobias; Cruse, Glenn (Frontiers in Veterinary Science, 2025)
IntroductionAccurate identification of eosinophils in tissue sections is required for diagnosis of eosinophilic esophagitis in humans and the assessment of severity of disease in allergy models. The pig may be a good model for sensitization and allergy models due to anatomical, physiological, and immunological similarities to humans. However, comparative studies on histochemical detection of eosinophils in fixed porcine tissue are lacking.MethodsQualitative and quantitative comparisons were performed for six histochemical methods previously reported for eosinophil and mast cell detection in other species. Astra Blue/Vital New Red, Congo Red, Luna, Sirius Red, Toluidine Blue, and modified regressive Hematoxylin & Eosin were applied to formalin-fixed paraffin embedded full-thickness sections of porcine esophagus. Specimens were collected from young, crossbred pigs sensitized to ovalbumin with or without subsequent oral exposure to ovalbumin to produce eosinophilic esophagitis lesions for comparison to non-allergic controls.ResultsEase of eosinophil quantitation was analyzed, and varied by histochemical stain, to determine whether stain selection increased accuracy and efficiency of evaluation. Noticeable differences in color contrast between intracytoplasmic granules, surrounding tissue, and cellular components aided detection and identification of eosinophils and mast cells with Astra Blue/New Vital Red and Toluidine Blue, respectively. For eosinophils, Congo Red and H&E were adequate, while Luna and Sirius Red presented challenges for quantitation.DiscussionIn this case, rapid and reliable characterization of porcine esophageal allergy models was made possible by using Astra Blue/New Vital Red for eosinophils and Toluidine Blue for mast cells.